Empanelment: A Novel Healthcare Initiative - Viewpoint - KC, Sarita (Medical Journal of Shree Birendra Hospital, 2022)
Military hospital management in Nepal faces challenges to meet the rising demands for quality care while enhancing efficiency and effectiveness as well as maintaining a workforce capable of meeting both peacetime and wartime needs. Empanelment of a tertiary civil hospital at a military regional command hospital is presented as an innovative strategic arrangement for leveraging productivity. Patient data for the first six months is analysed and key empanelment implementation issues are presented to enhance performance of healthcare providers.